Mitochondrial defects in proteasome and COP9 mutants - Fontes, Adriana Filipa da Silva (2015)
The aim of this work is the study of phenotypic changes and mitochondrial morphology in Saccharomyces cerevisiae cells with specific mutations in genes involved in the ubiquitin-proteasome pathway. The protein turnover is important because it ensures organelles viability such as mitochondria, indispensable for cell survival. The COP9 complex is paralogous to the proteasome lid and eukaryotic translational initiator factor 3 (eIF3) complexes. The CSN5 subunit of the COP9 signalosome is responsible for the E3 ligase Cdc53/Cul1 activity through the removal of the ubiquitin-like protein, Rub1. Deletion of the Csn5 gene is lethal in high eukaryotes but not in yeast, this observation allow us to study the effects of this mutation in this organism (strain Δcsn5) together with other mutants or double mutants: rpn11-m1, Δrub1, rpn11-m1/Δcsn5 rpn11-m1/ Δrub1. Mutants and wildtype (W303-1A) were characterised regarding growth in different carbon sources and temperature as well as response to stress or DNA damage causing agents (methyl methanesulfonate and canavanin). The morphological results allowed us to investigate authophagy, and in particular mitophagy, through fluorescence microscopy (GFP-Atg8 and GFP-Atg32) and Western Blot analysis. We found a relation between deubiquitination undertaken by Rpn11 protein, from the 19S proteasome subunit, and the activation of rubylation/derubylation cycles by the CSN5 subunit of the CSN complex (COP9 signalosome). In fact, the rpn11-m1/ Δrub1 shows a semi-lethal phenotype and mitophagy in exponential phase in glucose rich medium. Also the Δcsn5 strain shows early mitophagy together with phenotypic changes, such as big vacuoles. In addition, it has been established a possible relationship between the CSN complex and the resilience to damage in the DNA caused by the methylating agent, methyl methanesulfonate (MMS).